Association of Patient-Reported Health Status With Long-Term Mortality After Transcatheter Aortic Valve Replacement: Report From the STS/ACC TVT Registry. (December 2015) - Arnold, Suzanne V.; Spertus, John A.; Vemulapalli, Sreekanth; Dai, Dadi; O'Brien, Sean M.; Baron, Suzanne J.; Kirtane, Ajay J.; Mack, Michael J.; Green, Philip; Reynolds, Matthew R.; Rumsfeld, John S.; Cohen, David J.
Abstract : Background—: Although transcatheter aortic valve replacement (TAVR) is an effective treatment for aortic stenosis, long-term mortality after TAVR remains high and challenging to predict. The Kansas City Cardiomyopathy Questionnaire (KCCQ) is a health status measure, assessed directly from patients, that integrates 2 clinically relevant factors (symptoms and functional status) that may predict TAVR outcomes. Methods and Results—: Among 7769 patients from 286 sites in the Society of Thoracic Surgeons (STS)/American College of Cardiology (ACC) Transcatheter Valve Therapy (TVT) Registry, we examined the association between preprocedure (baseline) patient health status, as assessed by the KCCQ, and 1-year mortality after TAVR. The KCCQ Overall Summary Score was categorized as very poor: <25, poor: 25 to 49, fair: 50 to 74, or good: ≥75. Before TAVR, health status was rated as very poor in 28%, poor in 38%, fair in 24%, and good in 10%. Patients with worse health status were more likely to be women and had more comorbidities and higher STS mortality risk scores. Compared with those with good health status before TAVR and after adjusting for a broad range of baseline covariates, patients with very poor health status had a 2-fold increased hazard of death over the first year after TAVR (adjusted hazard ratio, 2.00; 95% confidence interval, 1.58–2.54), whereas those with poor and fair health status had intermediate outcomes (adjusted hazard ratio, 1.54; 95% confidence interval, 1.22–1.95 and adjusted hazard ratio, 1.20; 95% confidence interval, 0.94–1.55, respectively). Conclusions—: In a national, contemporary practice cohort, worse preprocedure patient health status, as assessed by the KCCQ, was associated with greater long-term mortality after TAVR. These results support the measurement and integration of the KCCQ into mortality risk assessments for patients considering TAVR. Abstract : Supplemental Digital Content is available in the text.